2016
DOI: 10.1088/1478-3975/13/6/066008
|View full text |Cite
|
Sign up to set email alerts
|

A minimal titration model of the mammalian dynamical heat shock response

Abstract: Environmental stress, such as oxidative or heat stress, induces the activation of the heat shock response (HSR) and leads to an increase in the heat shock proteins (HSPs) level. These HSPs act as molecular chaperones to maintain cellular proteostasis. Controlled by highly intricate regulatory mechanisms, having stress-induced activation and feedback regulations with multiple partners, the HSR is still incompletely understood. In this context, we propose a minimal molecular model for the gene regulatory network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(45 citation statements)
references
References 56 publications
0
45
0
Order By: Relevance
“…In contrast, models of the heat shock response in HeLA cells rely on lower resolution experimental data . While some of these models explicitly account for multiple processes in great detail (Abravaya et al, 1991), it has been argued that a minimal model that limits the number of degrees of freedom and uses a coarse-grained description of the underlying molecular processes suffices to explain these data (Sivéry et al, 2016). In this paper, we demonstrated that a favorable combination of highresolution experimental data and a minimal model can help in uncovering the essential determinants of the HSR dynamics.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, models of the heat shock response in HeLA cells rely on lower resolution experimental data . While some of these models explicitly account for multiple processes in great detail (Abravaya et al, 1991), it has been argued that a minimal model that limits the number of degrees of freedom and uses a coarse-grained description of the underlying molecular processes suffices to explain these data (Sivéry et al, 2016). In this paper, we demonstrated that a favorable combination of highresolution experimental data and a minimal model can help in uncovering the essential determinants of the HSR dynamics.…”
Section: Discussionmentioning
confidence: 90%
“…Previous models that place HSF-1 titration by HSPs at the center of HSR regulation identified three operating regimes of HSR and related them with normal, acute, and chronic stress conditions (Sivéry et al, 2016;Sriram et al, 2012). These three regimes are characterized by inactivation, partial activation, or saturation of HSP promoters by HSF-1, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a minimal description HSRN involves three different species: (i) MisFolded proteins (MFP) that are heat-induced and (ii) HSP which helps to refold MFP and (iii) HSF1 that promotes transcription of HSP. The dynamics of the network is mainly regulated by two complexes that both involve the chaperon HSP (Sivéry et al , 2016): HSPs titrate the MFP on the one hand and its own transcription factor (HSF1) on the other. Our model accounts for the temporal evolution of copy number of four molecular species (MFP; HSP mRNA; HSF1; HSP).…”
Section: Resultsmentioning
confidence: 99%
“…The heat stress cellular response dynamic is mainly regulated by two complexes that both involve the chaperone proteins HSP (Sivéry et al , 2016). HSPs titrate the misfolded proteins, on the one hand, and its own transcription factor (HSF1) on the other.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation